Perencanaan Desain Kapal Wisata Catamaran di Taman Nasional Bunaken Provinsi Sulawesi Utara - Kaeng, Andrew Julio Peter; Pusaka, Augustinus Kindangen (Departemen Teknik Sistem Perkapalan, Universitas Hasanuddin, 2026)
Marine ourism is a strategic sector that requires safe, comfortable, and environmentally friendly maritime transportation systems. This study aims to design a catamaran-type tourist vessel equipped with an underwater observation (glass-bottom) facility to enhance the tourist experience without requiring diving activities. The design methodology involves literature review, field data collection, and technical analyses, including principal dimension determination, hydrostatic calculations, stability assessment, and resistance analysis. The vessel is designed with a length between perpendiculars (Lpp) of 20 m, waterline length (Lwl) of 19.44 m, breadth of 10 m, draft of 1.5 m, and depth of 3 m. At a service speed of 9 knots, the required propulsion power is 531.642 HP using DF 325 ATX engines. The vessel is planned to operate on short-distance tourism routes of approximately 0.03 nautical miles with high daily trip frequency. The results indicate that the proposed design satisfies technical and operational requirements, including multihull stability criteria in accordance with applicable regulations. The catamaran configuration provides high transverse stability, shallow draft, and a spacious deck that enhances passenger comfort. In addition, the integration of underwater viewing facilities increases tourism value while minimizing environmental impact. Consequently, the proposed vessel demonstrates strong potential to support sustainable marine tourism development in Bunaken National Park